Alcohol, Everyday Activities, and Recognizing the Risk of a Few Drinks. (September 2015) - Burhans, Charles G.; Frantz, J. Paul; Rhoades, Timothy P.; Shah, Raina J.; Wise, Michael J.
How many drinks are too many drinks? This study explored this question from multiple perspectives. An earlier study of university students was expanded to a national adult sample of 191 adults. Participants were asked how many drinks they could consume before they would no longer feel safe engaging in everyday activities, including driving, biking, and walking. Compared to university students, a national adult sample generally considered activities to be unsafe at lower levels of alcohol consumption. This sample also tended to underestimate the number of drinks required to reach a blood alcohol concentration (BAC) of 0.08%. Some participants indicated an unwillingness to engage in activities if alcohol posed any increased risk, while others appeared to tolerate some added risk posed by alcohol consumption. Implications for risk perception and decision-making are discussed.